Experiencias de acercamiento al concepto de muerte en la infancia. Una mirada desde el enfoque de la Psicología Humanista y la Psicoterapia Existencial de Irvin Yalom (2019)
The main objective of this article was to develop a theoretical contribution to the concept of death in children, it sustained from those theories of the Humanistic Psychology and Existential Psychotherapy. An initial background search was carried out, which made it possible to show multiple difficulties in the articles and proposals investigated. Highlighting mainly two factors: the little theoretical advance that the topic of the concept of death in children has had and, the few investigations that have been developed from the Humanistic Psychology in front of it, taking into account precisely that death is for this approach, one of the existential properties of the human being. In first instance, an articulation has been made between the theorists Yalom and Villanueva, that allowed to show the way in which the concept of death since childhood is developed, finding that unlike what different authors propose, it would be around 6 months of age in which the child will have his first contact with death, advancing in its development until reaching a clear and consolidated concept. Finally, authors such as Rogers, Maslow, Yalom and Villanueva consider that death is experienced in childhood as a frustration that ranges from a minimum experience to a maximum one that can, depending on the degree of frustration generated in the infant, help to integrate and empower human beings or, on the contrary, stagnate their development and de-structure their psyche